Analisis Spasial Determinan Ketimpangan Distribusi Pendapatan Antarwilayah Tahun 2022 - Falahuddin, Muhammad Ilzam; Zukhrufah, Awika Yuliati; Sitanggang, Claudia Janefer Romora; Pusponegoro, Novi Hidayat (Seminar Nasional Official Statistics, 2024)
National development is a step that leads to an increase in the welfare of society. The success of development is measured through gross domestic product (GDP) which illustrates the level of economic growth. A high GDP increases per capita income. Economic growth must be balanced with the stability of the number of poor people to avoid income inequality. Java is the center of government and economy in Indonesia. Java is the largest contributor to Indonesia's GDP. The large contribution of GDP in Java is accompanied by income inequality in the region. This study aims to identify the existence of spatial effects on income inequality among districts/cities in Java Island and analyze the factors that affect income inequality in Java Island by considering spatial effects. The analysis shows that HDI, construction cost index, minimum wage, and per capita income affect income distribution inequality in Java. There is spatial interaction among 119 districts/cities in Java Island with Spatial Error Model (SEM).